If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 = 2h + -7 + 7 Reorder the terms: 60 = -7 + 7 + 2h Combine like terms: -7 + 7 = 0 60 = 0 + 2h 60 = 2h Solving 60 = 2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2h' to each side of the equation. 60 + -2h = 2h + -2h Combine like terms: 2h + -2h = 0 60 + -2h = 0 Add '-60' to each side of the equation. 60 + -60 + -2h = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -2h = 0 + -60 -2h = 0 + -60 Combine like terms: 0 + -60 = -60 -2h = -60 Divide each side by '-2'. h = 30 Simplifying h = 30
| 2x^2-4x+p=0findvaluesp | | x^3-12x^2+60x-48=0 | | -10.5z-63=2z-15 | | 2n+7=5n-8 | | (x*10)/100=110-x | | 2(4a+5)+134=80(a+9) | | 4a2-a/a | | y=99.828x | | log(x)=1.79 | | 2.0317x^2+65.56x=0 | | y=2.0317x^2+65.56x | | 5x-19=2x+12 | | 21/57 | | f(x)=x(2x-1)(x+4) | | 2sin(x)=2-3cos^2(x) | | 40-19=3(x-4) | | 8-72y=95-15y | | 7x^2+2x-15=0 | | Y(1-x)DX+x(1+y)dy=0 | | 2t+4u=40 | | 27-17=5(x-8) | | 20x-16=18x+6 | | -(13+g)=-9 | | 61+4y-28=15y-9-4y | | 80=91x | | 2.9y+1.7=3.5+23y | | -2(-3x-1)-3=-4 | | 9y-9=7y+1 | | x+18+4x=-48-4x-51 | | 4(7x+5)-48x=10x-10 | | 9p+8q=108 | | 6x-12=4(x+7) |